This party is political: the moving politics of the queer dancefloor in 120 BPM (2017). (3rd April 2022) - Pember, Alice
ABSTRACT: This article addresses the connection between the activism of AIDS advocacy group ACT UP and the house music scene of 1990s Paris as presented in 2017 AIDS drama 120 BPM . The article mobilizes Jacques Rancière's political and aesthetic philosophy alongside a phenomenological reading of dance and music to reveal how 120 BPM 's cinematic dancefloors construct cinematic politics. My reading suggests that the club scenes' mobile camerawork and soundscape of remixed queer club anthems engages viewers in an affective, queer 'club time' that ruptures the straightforward, linear timeline of the film's fictional narrative. Although Campillo has questioned his film's capacity to 'mobilise people today', this article suggests that a phenomenological approach to the 'queer time' effected by the music and movement in the film's club scenes reveals 120 BPM 's dancefloors as sites of embodied politics that transcend the specificity of the film's cultural and historical context.